Pengaruh Budaya Organisasi Terhadap Motivasi Penari Pada Sanggar Seni Budaya Besapen Kabupaten Tulang Bawang - Andy Fitriyadi Dharma Tilaar (LPPM STIE KRAKATAU, 2018)
One way to preserve Lampung culture is by collecting culture. Some forms of culture that are lost include dance, literature, language, and social procedures. So after examining it further in theory, the writer draws on the model in a research problem, namely the Influence of Organizational Culture on the Motivation of Dancers in the BESAPEN Cultural Art Studio, Tulang Bawang Regency. The hypothesis of the research that was successfully made by the author was that there was a positive influence from the Organizational Culture by the Tulang Bawang Regency Culture and Tourism Office on the motivation of the BESAPEN Cultural Arts Studio, Tulang Bawang Regency. The type of research in this thesis is an evaluation of Organizational Culture on the motivation of the BESAPEN Cultural Art Studio, Tulang Bawang Regency, After analyzing the data obtained from this study is the calculation results obtained by the value that t-count> t-table. This shows that the coefficient of each independent variable is statistically important in its effect on the dependent variable. The coefficient of determination (R2) is relatively moderate, that is 69.3% (percent) of the variation in motivation changes in the BESAPEN Cultural Art Studio, Tulang Bawang Regency can be explained by the independent variable, namely the behavioral approach. So it can be concluded that every Organizational Culture that is carried out has an influence on the motivation of members of the BESAPEN Cultural Art Studio in Tulang Bawang Regency.